Possible Compartmental Cytokine Release Syndrome in a Patient With Recurrent Ovarian Cancer After Treatment With Mesothelin-targeted CAR-T Cells. Issue 3 (April 2017) - Tanyi, Janos L.; Stashwick, Caitlin; Plesa, Gabriela; Morgan, Mark A.; Porter, David; Maus, Marcela V.; June, Carl H.
Abstract : Cytokine release syndrome (CRS) is a potentially severe systemic toxicity seen after adoptive T-cell therapy and caused by T-cell activation and proliferation and is associated with elevated circulating levels of cytokines such as C-reactive protein, interleukin-6 (IL-6), and interferon-γ and has previously been described as a systemic response in hematologic malignancies. A 52-year-old woman with BRCA 1 mutation positive heavily pretreated advanced recurrent serous ovarian cancer was treated under a compassionate use protocol with autologous mesothelin-redirected chimeric antigen receptor T cells (CART-meso). Autologous T cells were transduced to express a receptor composed of an extracellular antimesothelin single-chain variable fragment fused to 4-1BB and TCR-zeta signaling domain. This patient was infused with 3×10 7 CART-meso T cells/m 2 without lymphodepletion and developed compartmental CRS confined to the pleural cavities. The compartmental CRS was evidenced by an increase in IL-6 and accumulation of CART-meso T cells in pleural fluid compared with peripheral blood and was successfully treated the anti-IL6 receptor antagonist tocilizumab on D21 after the T-cell infusion. This is the first description of a compartmental CRS in a patient with solid malignancy. This response could be due to malignant pleural fluid creating an environment where T cells could interact with tumor cells and suggests localized on-target CAR-T-cell activation.